Factors associated with test failure in pregnant women undergoing cell-free DNA-based testing for fetal trisomy. (December 2021) - Chang, Jiazhen; Qi, Qingwei; Zhou, Xiya; Jiang, Yulin; Hao, Na; Liu, Juntao
Objective: To investigate the factors associated with cell-free DNA test failure, and the optimal subsequent management of these pregnancies. Methods: This was a retrospective study of 27, 363 singleton pregnancies undergoing cell-free DNA testing. Women with cell-free DNA test failure were divided into a high-risk group and a low-risk group according to their indications. The subsequent management and pregnancy outcomes of these women were followed up. Results: The rate of cell-free DNA test failure at the first sampling was 1.49%, and 78.4% of failures were due to a low fetal fraction. Of the 66 women who refused any subsequent management, an adverse pregnancy outcome was seen in 5 cases, all belonging to the high-risk group. Of the 13 low-risk women who chose second-trimester maternal serum screening, all obtained a low-risk maternal serum screening result and an unaffected pregnancy outcome. A redraw was chosen by 171 women, which yielded a result in 75.4% and their pregnancy outcomes were unaffected; 42 women had an uninformative result again and received an amniocentesis. As 158 women had an amniocentesis after the first sampling, this procedure was offered in 200 cases altogether. Abnormal genetic testing results were shown in six (3%, 6/200) cases, all in the high-risk group. Conclusions: High-risk pregnant women with cell-free DNA test failure are at increased risk of adverse pregnancy outcomes. A second sampling for cell-free DNA test or maternal serum screening might be suggested to low-risk women. Invasive prenatal diagnosis should be offered to the high-risk patients, especially those with a second cell-free DNA test failure.